Records of birds in Quang Nam Chau proposed Species and Habitat conservation area, Quang Ninh province, northeastern Vietnam - Trung Thanh Hoang; Khac Quyen Le; Ngoc Tu Ly; Manh Truong Ha (Tạp chí Khoa học Đại học Huế: Khoa học Tự nhiên)
Quang Nam Chau is a proposed species and habitat conservation area located in Quang Ninh province, northeastern Vietnam. The area is covered by primary forest and plays an important role in watershed protection. However, there has not been any previous ornithological study conducted in the area. This study was carried out in October and November 2021 to investigate the diversity of bird species and identify the current threats to avifauna and biodiversity in Quang Nam Chau. A total of 121 bird species belonging to 47 families and 17 orders were identified, with Passeriformes (73 species, 60.3%) and Muscicapidae (11 species, RDi = 9.09) being the most diverse order and family, respectively. Five of the 121 recorded species were globally threatened, and 29 were nationally rare and/or threatened. The avifauna and general biodiversity of the region are threatened by illegal hunting and trapping, agriculture expansion, grazing, and non-timber resource exploitation.